Mercury and amino acid content relations in northern pike (Esox lucius) in subarctic lakes along a climate-productivity gradient - Kozak, Natalia; Kahilainen, Kimmo K.; Pakkanen, Hannu K.; Hayden, Brian; Østbye, Kjartan; Taipale, Sami J. (Environmental Research, 2023)
Mercury is a highly toxic element for consumers, but its relation to amino acids and physiology of wild fish is not well known. The main aim of this study was to evaluate how total mercury content (THg) of northern pike (Esox lucius) is related to amino acids and potentially important environmental and biological factors along a climateproductivity gradient of ten subarctic lakes. Linear regression between THg and sixteen amino acids content [nmol mg-1 dry weight] from white dorsal muscle of pike from these lakes were tested. Lastly, a general linear model (GLM) for age-corrected THg was used to test which factors are significantly related to mercury content of pike. There was a positive relationship between THg and proline. Seven out of sixteen analysed amino acids (histidine, threonine, arginine, serine, glutamic acid, glycine, and aspartic acid) were significantly negatively related to warmer and more productive lakes, while THg showed a positive relationship. GLM model indicated higher THg was found in higher trophic level pike with lower cysteine content and inhabiting warmer and more productive lakes with larger catchment containing substantial proportion of peatland area. In general, THg was not only related to the biological and environmental variables but also to amino acid content. Peer reviewed